Cross-reactivity of 4CMenB vaccine-induced antibodies against meningococci belonging to non-B serogroups in Italy - Cecilia Fazio; Alessia Biolchi; Arianna Neri; Sara Tomei; Paola Vacca; Luigina Ambrosio; Annapina Palmieri; Elena Mori; Rita La Gaetana; Mariagrazia Pizza; Marzia Monica Giuliani; Laura Serino; et al. (Taylor & Francis Group, 2021)
The four-component meningococcal serogroup B vaccine (4CMenB) contains antigens present in the majority of meningococci causing invasive meningococcal disease (IMD) and may potentially offer protection against strains belonging to non-B serogroups. This study aimed to evaluate the ability of 4CMenB-induced antibodies to kill, in a human serum bactericidal assay (hSBA), non-B meningococci belonging to the main genotypes responsible for IMD in Italy. Meningococci, collected between 2015 and 2017, was characterized for PorA, FetA and sequence type, and for clonal complex. Twenty non-B isolates, representative of the most frequent genotypes, were molecularly characterized for 4CMenB antigens and tested in hSBA with sera from 4CMenB-vaccinated infants and adolescents. Among twenty isolates, eleven were serogroup C, five were Y, two W and two X. All isolates contained genes encoding for fHbp and NHBA antigens and four harbored the NadA full-length encoding gene. Positive hSBA titers were obtained against all serogroup W, X and Y isolates and against five serogroup C isolates. These data show that the 4CMenB vaccine can induce bactericidal antibodies against genetically representative meningococcal W, Y and X strains from Italy. For serogroup C, different susceptibilities to killing were observed for strains with similar antigenic repertoires.